2006
DOI: 10.1002/ejlt.200500262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of some rancidity measures at the end of the shelf life of sunflower oil

Abstract: Identification of some rancidity measures at the end of the shelf life of sunflower oilSunflower oil was stored at 40 7C, and changes in peroxide value (PV), anisidine value (AnV), thiobarbituric acid (TBA) value, iodine value (IV), conjugated dienes (CD) and hexanal (Hex) levels were monitored. Changes in the odor of samples during storage were assessed sensorially. Apart from IV, which decreased as storage progressed, the other chemical rancidity measures increased. Sensory shelf life data were adequately de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
2
22
0
2
Order By: Relevance
“…Fatty acid composition of sunflower seed oil has been reported by a number of scientists to vary with planting location and with climatic conditions during the growing season. Sunflower oil content of fatty acids presented in this study is similar to that of Samarth and Mahanwar [26], Makhoul et al [27] and Hosein et al [28] who reported that sun flower oil contained palmitic (5.81-8.0%) stearic (3.35-6.3%) oleic (23.81-42.6%) and linoleic (46-65.73%) acids.…”
Section: Effects Of Gamma-irradiation On Fatty Acid Of Sunflower Oilsupporting
confidence: 89%
“…Fatty acid composition of sunflower seed oil has been reported by a number of scientists to vary with planting location and with climatic conditions during the growing season. Sunflower oil content of fatty acids presented in this study is similar to that of Samarth and Mahanwar [26], Makhoul et al [27] and Hosein et al [28] who reported that sun flower oil contained palmitic (5.81-8.0%) stearic (3.35-6.3%) oleic (23.81-42.6%) and linoleic (46-65.73%) acids.…”
Section: Effects Of Gamma-irradiation On Fatty Acid Of Sunflower Oilsupporting
confidence: 89%
“…In general, PV decomposes at high temperatures and forms the secondary oxidation products. This phenomenon has been observed in most deep-fat frying studies (Pantzaris 1997;Makhoul et al 2006). Even though PV rose and fell throughout frying periods, the PV was significantly higher (P<0.05) in RBD palm olein (system I) than both palm-based MLCT oil (systems II and III), indicating that RBD palm olein was less thermal-resistant to oxidation ( Table 2).…”
Section: Changes In Color and Rancimat Ipmentioning
confidence: 69%
“…Since lipid oxidation is a critical factor for food quality and prolonged shelf-life of edible oils, many studies have concentrated on the prevention of lipid oxidation by natural antioxidants (NA) (Baydar, Özkan, & Yasar, 2007;Ebrahimabadi, Djafari-Bidgoli, Mazoochi, Kashi, & Batooli, 2010;Rodríguez Vaquero, Tomassini Serravalle, Manca de Nadra, & Strasser de Saad, 2010). Recently, much effort has been made to prevent the lipid oxidation for sunflower oil in conjunction with some synthesized food additives (Guilleän, Cabo, Ibargoitia, & Ruiz, 2005;Iqbal, & Bhanger, 2007;Makhoul, Ghaddar, & Toufeili, 2006). However, few studies about the application of natural antioxidants to microencapsulated edible oils have been reported.…”
Section: Introductionmentioning
confidence: 96%